Self-concept of cervical cancer patients after chemotheraphy in Yogyakarta - Nur Azizah Indriastuti; Riski Oktafia; Novika Riswanti (Journal of Health Technology Assessment in Midwifery, 2021)
Cervical cancer is one of the deadliest types of cancer that attacks women in the world. One of the treatment efforts for cancer is chemotherapy. Patients with cervical cancer who receive chemotherapy more than twice will experience impaired self-concept. This study aims to determine self-concept in cervical cancer patients who have undergone chemotherapy in Yogyakarta. This research uses qualitative method with phenomenology approach. Data collection is done with interview and observation. Participants totaling five people were determined by purposive sampling. The validity of the data used source triangulation and checked the data back to the participants. Analysis of data were by comparing among categories, marking and describing descriptively. The results of the study are 6 themes, namely physical changes, emotional changes, changes in sexual relations, changes in relationships with family, changes in the role of parenting and social changes in society. The impact of chemotherapy causes various changes in cervical cancer patients which make the self-concept of cervical cancer patients undergo changes